The co-op : a novel - DeWitt, Tarah (St. Martin's Griffin, 2024)
"They say love and construction don't mix. By that logic, hate and construction may as well be condemned. LaRynn Lavigne and Deacon Leeds had one short and contentious summer fling when they were teens-certainly nothing to build a foundation on. But a decade later, when their grandmothers have left them with shared ownership of their dilapidated Santa Cruz building, they're thrust back together and have to figure out how to brace up the pieces. LaRynn has the money, but in order to access her trust, she has to be married. Deacon has the construction expertise, but lacks the funds. A deal is struck: Marry for however long it takes to fix up the property, collect a profit, and cut ties. Thrust into a home without walls, LaRynn and Deacon quickly learn that it's easy to hide behind emotional ones, even in a marriage. But with all the exposure and pitfalls that come with living with the opposite sex (and none of the perks, much to their growing mutual frustration) they'll also have to learn what it means to truly cooperate as a team. Filled with crackling tension, The Co-op is a steamy second chance romance about restoration and renovation, and uncovering all the things that build character within ourselves. It's about the never-ending construction project that partnership is, and finding enjoyment at every stage"--